2021
DOI: 10.1055/a-1326-2125
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is Associated with Poor Covid-19 Outcomes: A Systematic Review and Meta-Analysis

Abstract: Our aim was to assess the association between obesity and the risk of unfavourable outcomes (composite of severe disease and mortality) in inpatients with COVID-19. We conducted a systematic search of databases between December 2019 and 28th June 2020. Studies were included if they reported or allowed estimation of an odds ratio (OR) for unfavourable outcome in obese compared to non-obese patients hospitalised for COVID-19. Twenty cohort studies of 28 355 hospitalised patients with COVID-19 infection were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…The results of this study suggest that significant positive relationships exist between the point prevalence of depression and obesity and the COVID-19 crude mortality rate across countries. These results are consistent with the results of earlier research which has found that both these disorders confer an added risk of mortality in COVID-19 patients [13,[17][18][19]28,29]. On bivariate analyses, sugar consumption was also associated with the crude mortality rate; however, on multivariate analyses, this relationship, unlike the former two, was no longer statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study suggest that significant positive relationships exist between the point prevalence of depression and obesity and the COVID-19 crude mortality rate across countries. These results are consistent with the results of earlier research which has found that both these disorders confer an added risk of mortality in COVID-19 patients [13,[17][18][19]28,29]. On bivariate analyses, sugar consumption was also associated with the crude mortality rate; however, on multivariate analyses, this relationship, unlike the former two, was no longer statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…In a similar manner, evidence has emerged linking obesity with increased mortality in patients with COVID-19 [28,29]. This association appears to be consistent across countries, and is significant even after controlling for associated conditions such as diabetes mellitus or systemic hypertension [12].…”
Section: Introductionmentioning
confidence: 70%
“…The wealth of evidence is such that more than a dozen meta-analyses have been conducted on this topic, for example [ 5 , 6 ]. The reported levels of risk, however, vary somewhat between studies as differing study populations—population based versus hospital based—can lead to differing findings with the latter being less informative of risks in the general population as patients in hospital with COVID represent a high-risk group with more severe manifestations, and decisions to admit to hospital are influenced by varying, often health system specific, factors.…”
Section: Epidemiologymentioning
confidence: 99%
“…In our cohort, all obese patients had SARS-CoV-2 RNA detected in stools. Obesity is one of the main risk factors for severe COVID-19 and poor clinical outcomes[ 20 , 21 ], and is associated with a strong inflammatory response both in the general population and in COVID-19 patients[ 22 ]. This could justify a more prolonged viral shedding in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%